Handgrip strength: comparative analysis between elderly hospitalized for non-surgical conditions and healthy - Wietzke, Mônica (2024)
Justification and objectives: Aging is characterized as a dynamic process in which morphological and physiological changes occur in the body. The increase in longevity caused a higher incidence of chronic diseases, health problems and hospital admissions in this population. Aging causes a gradual reduction in muscle mass and strength, which can be obtained from the handgrip strength (HPF) measured by dynamometry. The present study aimed to comparatively analyze HPF between elderly people hospitalized for non surgical conditions and healthy elderly people. Methods: Elderly people of both sexes were allocated in the Hospitalized Group (GH) those individuals hospitalized under non-surgical conditions and in the Control Group, the healthy elderly. The HPF was evaluated by manual hydraulic dynamometry. Results: Sample (n=51) (GH: n= 16; CG: n= 35) with a mean age of 70.7±7.3 years and a body mass index of 26.2±3.6 kg/m2. The difference between the analyzed groups was evidenced in terms of HGS both in absolute value (p=0.016) and in its predicted value (p=0.001), having been lower in GH. Conclusion: Elderlypeople in non-surgical conditions have reduced peripheral muscle strength compared to healthy individuals, which demonstrates the need for care aimed at the functional recovery of this population in the hospital environment.